Implementation and Evaluation of a Values Clarification Activity for a Large Undergraduate Human Sexuality Course. Issue 1 (2nd January 2016) - Lederer, Alyssa M.
ABSTRACT: Values clarification is an important tool that helps individuals to clarify their beliefs about sexuality-related issues. This lesson plan provides instructions for a 1-hour values clarification activity for a large undergraduate human sexuality course that serves as an introduction to course content and tone, stimulates students' initial thinking about course topics, and demonstrates the diversity of perspectives on sexuality-related issues. Survey-based evaluation findings (N = 71) establish that the activity successfully meets its learning objectives and that students feel comfortable participating. Step-by-step directions, recommendations for facilitation, and reflections on best practices for the activity are provided.